Profesionalni razvoj učiteljev razrednega pouka - Obran, Monika; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2010)
Professional development of class teachers. The article discusses what teachers think about their current knowledge, their further education and further professional development. The theoretical part presents what the professional development of a teacher means, when it begins and which models of professional development have already been researched. Furthermore, a discussion is included about why every teacher should take care of their professional development, which consequentially, influences the development of their personalities. The goal of the empirical part was to research the class teachers' opinions about their current knowledge and experience. Furthermore, research was done on the extent that the teachers are aware of the importance of lifelong learning and their ways of taking care of their professional development. A discussion is included on whether there is a difference between a teachers' education and their period of employment. The method of gathering information for the results was used by means of a questionnaire, which consisted of 15 statements in the form of a 5-level scale. Descriptive and causal-non-experimental methods of pedagogical research were used.